(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper summarizes the theoretical and empirical research on how the introduction of derivative securities affects the underlying market. A wide array of theoretical approaches has been applied to the question of howspeculative trading, the introduction of futures, or the introduction ofoptions might affect the stability, liquidity and price informativeness ofasset markets. In most cases, the resulting models predict that speculativetrading and derivative markets stabilize the underlying market under certain restrictive conditions, but in general the predictions can go either way, depending on parameter values. The empirical evidence suggests thatthe introduction of derivatives does notdestabilize the underlying market—either there is no effect or there is adecline in volatility—and that the introduction of derivatives tends to improvethe liquidity and informativeness of markets. In this paper we analyze the effect of the introduction of derivatives(futures and options) in the Indian market on the volatility and on the trading volume of the underlying index. The period analyzedcovers from April 2001 to March 2006. To study this effect, we use three modelsof conditional volatility GARCH, EGARCH and GJR. We find significant impact on variance: the evidence indicates that the conditional volatility of the underlying index declines after derivativemarkets are introduced. The trading volume of NSE (National Stock Exchange of India) Nifty -50 increases significantly. Inaddition, the introduction of the derivative contracts in India confirms adecrease in uncertainty in the underlying market and an increase in liquidity,which possibly enhance their efficiency..